Recent developments in electrokinetics of salt-free concentrated suspensions. (August 2016) - Delgado, Ángel V.; Carrique, Félix; Roa, Rafael; Ruiz-Reina, Emilio
Abstract: In this work we present a brief revision of existing models on the electrokinetics, both dc and ac, of concentrated suspensions in so-called salt-free conditions. In the ideal description, this means that the suspension is constituted only by the particles, the neutral solvent and the ions released by the surface groups of the particles when they dissociate and provide the surface charge. A realistic description is also offered, in which, in addition, the presence of ions from water dissociation and atmospheric CO2 dissolution is considered. The differences between both approaches can be very significant. It is particularly in the volume fraction range below 1–10% that the dc electrophoretic mobility and conductivity are strongly dependent on the model. Concerning ac electrokinetic predictions, it is found that the alpha or concentration polarization relaxation is absent in ideal systems, which only show the Maxwell–Wagner–O'Konski (MWO) relaxation and, if the surface charge is high enough, also the MW process of the counterion condensate at high frequencies. An analysis is also performed on the role of finite ion size on the calculations, showing that it is significant only when the latter condensate relaxation is not negligible. The predictions of the models are checked against both aqueous and non-aqueous experimental data existing in the literature. In spite of the complexity of the systems studied, a remarkable agreement can be found, confirming the validity of the main hypothesis of the salt-free electrokinetic models. Graphical abstract: Highlights: The electrokinetics of salt-free systems is revised. dc and ac phenomena are considered. The role of water dissociation and dissolved CO2 is most important at low volumen fractions Models including consideration of finite-size ions are described. The agreement with existing experiments, both in aqueous and non-aqueous media is satisfactory.